Chondrocyte β‐Catenin Signaling Regulates Postnatal Bone Remodeling Through Modulation of Osteoclast Formation in a Murine Model. Issue 1 (January 2014) - Wang, Baoli; Jin, Hongting; Zhu, Mei; Li, Jia; Zhao, Lan; Zhang, Yejia; Tang, Dezhi; Xiao, Guozhi; Xing, Lianping; Boyce, Brendan F.; Chen, Di
<x xml:space="preserve">Abstract</x> Objective To investigate whether β‐catenin signaling in chondrocytes regulates osteoclastogenesis, thereby contributing to postnatal bone growth and bone remodeling. Methods Mice with conditional knockout (cKO) or conditional activation (cAct) of chondrocyte‐specific β‐catenin were generated. Changes in bone mass, osteoclast numbers, and osteoblast activity were examined. The mechanisms by which β‐catenin signaling in chondrocytes regulates osteoclast formation were determined. Results The β‐catenin cKO mice developed localized bone loss, whereas cAct mice developed a high bone mass phenotype. Histologic findings suggested that these phenotypes were caused primarily by impaired osteoclast formation, rather than impaired bone formation. Further molecular signaling analyses revealed that β‐catenin signaling controlled this process by regulating the expression of the RANKL and osteoprotegerin (OPG) genes in chondrocytes. Activation of β‐catenin signaling in chondrocytes suppressed Rankl gene transcription through a glucocorticoid receptor–dependent mechanism. The severe bone loss phenotype observed in β‐catenin cKO mice was largely restored by treatment with human recombinant OPG or transgenic overexpression of Opg in chondrocytes. Conclusion β‐catenin signaling in chondrocytes plays a key role in postnatal bone growth and bone remodeling through its regulation of osteoclast formation.